Perbedaan Kekuatan Geser Perlekatan (Shear Bond Strength) Antara Self – Adhering Flowable Composite dan Flowable Composite dengan Sistem Adhesif Self – Etch pada Dentin - Steven Tanjung; Rudy Djuanda; Angela Evelyna (Maranatha Christian University, 2019)
Restoration is a treatment to restore the structure of missing dental hard tissue due to caries. Flowable composite has good adaptability to the cavity wall so that it is widely used as an intermediate layer. Composite resins require an adhesive system to bond chemically with dental hard tissue. Self - adhering flowable composite combining etching, priming, and adhesive in one flowable package. This study was conducted with the aim to determine the difference in shear bond strength between Self – adhering flowable composite and flowable composite with self – etch adhesive system on dentine. The number of samples used was 38 pieces. After dentin was prepared and fixed, samples was divided into 2 groups, each group consisting of 19 samples. First group was applied with self – adhering flowable composite, second group was applied with flowable composite with self – etch adhesive system. Samples was immersed in pH 6.8 normal saline and stored for 24 hours, then dried and shear bond strength was tested using a universal testing machine. The data obtained were analyzed using independent t – test. The statistical analysis using independent t – test showed that there were significant differences in the shear bond strength between the two groups, p=0,000 (p<0.05). The study concluded that there is difference of shear bond strength between self – adhering flowable composite and flowable composite with self – etch adhesive system on dentine.